Test driven database development - Wheeler, David (O'Reilly, 2010)
"Creating a database schema means creating an interface for applications to use to manage their data. But how do you know how well that interface works until you've tried it? This video introduces the concept of test-driven development to database administrators. We'll use pgTAP to work through a real-world example creating a database design with an intuitive, useful interface for managing application data."--Product description page (viewed Oct. 18, 2010).